LO064: Simulation in Canadian postgraduate emergency medicine training — a national survey. (2nd June 2016) - Russell, E.; Hagel, C.; Petrosoniak, A.; Howes, D.; Dagnone, D.; Hall, A.K.
Abstract : Introduction: Simulation-based medical education (SBME) is an important training strategy in emergency medicine (EM) postgraduate programs yet the extent of its use is variable. This study sought to characterize the use of simulation in FRCP-EM residency programs across Canada.Methods: A national survey was administered to residents (PGY2-5) and program representatives (PR), either a program director or simulation lead at all Canadian FRPC-EM programs. Residents completed either paper or electronic versions of the survey, and PR surveys were conducted by telephone.Results: The resident and PR response rates were 60% (187/310) and 100% (16/16), respectively. All residency programs offer both manikin-based high fidelity and task trainer simulation modalities. Residents reported a median of 20 (range 0-150) hours participating in simulation training annually, spending a mean of 16% of time in situ, 55% in hospital-based simulation laboratories, and 29% in off-site locations. Only 52% of residents indicated that the time dedicated to simulation training met their training needs. All PRs reported having a formal simulation curriculum with a frequency of simulation sessions ranging from weekly to every 6 months. Only 3/16 (19%) of programs linked their simulation curriculum to their core teaching. Only 2/16 programs (13%) used simulation for resident assessment, though 15/16 (93%) PRs indicated they would be comfortable with simulation-based assessment. The most common PR identified barriers to administering simulation by were a lack of protected faculty time (75%) and a lack of faculty experience with simulation (56%). Both PRs and residents identified a desire for more simulation training in neonatal resuscitation, pediatric resuscitation, and obstetrical emergencies. Multidisciplinary involvement in simulations was strongly valued by both residents and PRs, with 76% of residents indicating that they would like greater multidisciplinary involvement.Conclusion: Among Canadian FRCP-EM residency programs, SBME is a frequently used training modality, however, there exists considerable variability in the structure, frequency and timing of simulation exposure for residents. Several common barriers were identified that impact SBME implementation. The transition to competency-based medical education will require a national, standardized approach to SBME that includes a unified strategy for training and assessment.